Analisis Pemikiran Ekonom Islam pada Masa Kontemporer: (Muhammad Nejatullah Siddiqi, Umer Chapra, Syed Nawab Haidar Naqvi) - Muhammad Iswan Kotta; Harun Alrasyid; Idris Parakassi; Fakhruddin Mansyur (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
This journal discusses contemporary Islamic economic thought through an in-depth analysis of three key figures: Muhammad Nejatullah Siddiqi, Umer Chapra, and Syed Nawab Haidar Naqvi. Islamic economics, based on Sharia principles, offers an alternative to secular economic systems that often focus solely on material profit. Siddiqi emphasizes the importance of a fair and sustainable Islamic financial system, focusing on the fulfillment of individuals' basic needs, justice in production and distribution, and the implementation of zakat in public finance. Chapra, as a pioneer of Islamic economics, proposes a principle of freedom balanced with responsibility, as well as the importance of socioeconomic reconstruction to achieve welfare. Meanwhile, Naqvi highlights the role of government in ensuring distributive justice and the elimination of riba. Through a qualitative descriptive approach, this research provides insights into the contributions of these three thinkers to the development of Islamic economic theory in the contemporary era.